Determinants and impact of automation. An analysis of robots' adoption in OECD countries (Paris, 2019)
"This report analyses automation trends and its effect on employment in OECD countries. On average, robots are found to be associated with a reduction in employment in elementary occupations – those requiring the lowest levels of skills – and an increase in employment in high-skill occupation such as professionals and technicians. For occupations in the middle of the skills distribution the correlation is strong and negative. In general, therefore, these estimates do not support the hypothesis of labour market polarisation, i.e.: an increase in both high-skill and low-skill employment. However, in a few countries - notably the United States - this report finds evidence of labour market polarisation."